Capacity Building Of Rural Society: The Contribution Of Pakuan University's Students In Enhancing Community Empowerment In Paseban Village - Sabila, Nova Putri; Larasati, Eliza; Kusumawardani, Shabriena Nindya; Faizah, Annissa Nur; Ryanti, Delva; Andria, Fredi (International Journal of Research in Community Services, 2024)
In the era of globalization, adapting to changes is crucial for individuals to compete in business development. Saung Lebah Madu Paseban, located in the village of Paseban, Megamendung, faces challenges due to limited human resource utilization attributed to a lack of skills, knowledge, and motivation among the locals. To address these issues, the community is being empowered through direct training and coaching activities, including practical sessions on making honey-based products like soap, jelly, and aromatherapy candles. Additionally, residents receive training in marketing and finance. The success of this empowerment initiative depends on the active participation and determination of the community members. Questionnaires distributed before and after the training sessions reveal that a significant number of individuals have genuinely benefited from the activities. The training outcomes demonstrate a clear improvement in the understanding and abilities of the participants, as evidenced by their honest feedback. Utilizing clustering analysis with the K-Means algorithm, participants are grouped into clusters based on their knowledge levels—cluster 1 (High Knowledge) and cluster 2 (Low Knowledge). Overall, the training not only enhances the community's understanding but also equips them with the skills to produce high-quality honey derivative products.